Energy diversity and nuclear energy for sustainable development in Turkey - Kok, Besir; Benli, Huseyin (Pergamon-Elsevier Science Ltd, 2017)
This study aims to investigate the effects of using nuclear and renewable energy on the economic growth of Turkey. In the last fourteen years, average growth of Turkish economy is up about 4.85%, annually. In relation to this, Turkish electricity demand has increased annually about 6%-8% during this period. This demonstrates the need for a sustainable energy policy to meet energy demand. Electricity sources of Turkey are mainly thermal and renewable. Natural gas and coal dominates to the other thermal sources. Turkey imports substantial amount of natural gas and coal mainly from Russia, Iran etc. This external dependence on energy resources has led to a continual increase in the current account deficit of Turkey. Therefore, Turkey needs to reduce its external dependency and find some new sustainable energy sources. Nuclear power generation in Turkey will reduce the dependency on energy generation in a significant way. In this study; Turkey's established power capacity and electricity generation have been investigated. The current state of the renewable energy resources of the country and the potential resources available and the nuclear energy in Turkey have been examined in detail. Published by Elsevier Ltd.
Keywords: Energy; Energy policy; Renewable energy; Turkey; Energy demand; Nuclear energy